2009
DOI: 10.1007/s11433-009-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

How random are matrix elements of the nuclear shell model Hamiltonian?

Abstract: In this paper we study the general behavior of matrix elements of the nuclear shell model Hamiltonian. We find that nonzero off-diagonal elements exhibit a regular pattern, if one sorts the diagonal matrix elements from smaller to larger values. The correlation between eigenvalues and diagonal matrix elements for the shell model Hamiltonian is more remarkable than that for random matrices with the same distribution unless the dimension is small. nuclear shell model, geometry property, linear correlation, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Shen et al studied the general behavior of matrix elements of the nuclear shell model Hamiltonian [84]. It is found that nonzero off-diagonal elements exhibit a regular pattern, if one sorts the diagonal matrix elements from smaller to larger values.…”
Section: Randomness Of Matrix Elements Of the Nuclear Shell Model Hammentioning
confidence: 99%
“…Shen et al studied the general behavior of matrix elements of the nuclear shell model Hamiltonian [84]. It is found that nonzero off-diagonal elements exhibit a regular pattern, if one sorts the diagonal matrix elements from smaller to larger values.…”
Section: Randomness Of Matrix Elements Of the Nuclear Shell Model Hammentioning
confidence: 99%
“…Thus it seems that the significant digit law takes precedence over physical statistics, and it might be a more fundamental principle behind the complexity of the nature. There are other sorts of regularities very interesting and not totally understood yet [30]. Before entering to the details of three statistics, we discuss the mantissa distribution firstly in the following section, as it is a closely relevant and vital issue to Benford's law.…”
Section: Introductionmentioning
confidence: 99%